Taxonomic research, collections and associated databases – and the changing science scene in New Zealand - Nelson, Wendy (New Zealand Science Review, 2016)
The past two years have seen very important developments in the New Zealand science system. In particular, in this period we have seen the establishment of the National Science Challenges, the launch of the National Statement of Science Investment (NSSI), the reconfiguration of the Ministry of Business, Innovation and Employment (MBIE) contestable research funds (now the Endeavour and Smart Ideas funds), and most recently the establishment in the 2016 Budget of the Strategic Science Investment Fund (SSIF). At present consultation is under way on ‘roadmaps’ for conservation and environmental science, for the primary sector, and for biosecurity, recognising the need for sound science to underpin policy and decision-making.